Factores de riesgo y su influencia sobre la infección intestinal por giardia lamblia en niños escolares. Unidad Educativa Rosa Briones Oyague. Recinto Santa Martha. Vinces. Los Ríos. octubre 2018-abril 2019 - Macías Aviléz, María Mercedes (2019)
Introduction: Intestinal parasites are a major health problem worldwide, among the most frequent are those produced by protozoa, especially Giardia lamblia, a parasite that causes diarrhea and inflammation in the duodenum and jejunum, is more frequent in children under five. years and 30% of adults. Objective: To determine the influence of risk factors on the existence of intestinal infection by Giardia lamblia in school children of the Educational Unit "Rosa Briones Oyague" Santa Martha campus. Vinces. Los Ríos, October 2018 - April 2019. Methodology: We used the inductive-deductive, historical-logical method and direct unstructured scientific observation, we worked with the total population consisting of 75 children from 5 to 12 years old, the survey was used and a coproparasitological examination of children for obtaining data. Results: It was obtained that the predominant sex of children who presented intestinal giardiasis was the male with 51.8% and the age range with the most children infected with Giardia lamblia were those from 7 to 9 years of age with 46.4%. Conclusions: Among the risk factors that influence the intestinal infection caused by Giardia lamblia in these children are the sanitary conditions of their homes, the lack of basic services, the inadequate prevention measures used by the family and the low frequency with which the Nursing staff in charge of this population carries out prevention and health promotion activities